JavaScript Unit Testing - Saleh, Hazem; Saleh, Hazem (Packt Publishing, 2013)
A practical, example-driven guide to using, automating, and integrating JavaScript Unit tests for the busy and conscientious JavaScript developer striving for excellence and success. JavaScript Unit Testing is a must have guide for every web developer, designer, architect, and JavaScript coder seeking to ensure the highest quality of their web applications and JS code. Knowledge of JavaScript is assumed.